Association of high-risk sexual behaviours with sexually transmitted infections among men who have sex with men living with HIV. (6th May 2022) - Raccagni, Angelo Roberto; Poli, Andrea; Galli, Laura; Spagnuolo, Vincenzo; Bruzzesi, Elena; Muccini, Camilla; Gianotti, Nicola; Canetti, Diana; Mainardi, Ilaria; Castagna, Antonella; Nozza, Silvia
Abstract : Objectives: To explore different sexual behaviours as risk factors for STI among men who have sex with men (MSM) living with HIV. Methods: This is a cross-sectional study on MSM living with HIV followed at the Infectious Diseases Unit of San Raffaele Hospital, Milan, with at least one diagnosis of gonorrhoea, syphilis, chlamydia or anal human papilloma virus (HPV), between July 2016 and February 2021. We conducted a survey on high-risk sexual behaviours with regard to (1) mean number of partners per month, (2) estimated percentage of condom use and (3) most frequent type of sexual intercourse during 2016–2021. Data on these variables were grouped as follows: (1a) ≤5 vs >5, (1b) >10 vs ≤ 10, (2a) 0% vs >0%, (2b) ≤50% vs >50%, (2c) 100% vs <100%, (3a) ≥50% vs <50% receptive, (3b) 100% vs <100% insertive, and (3c) 100% vs <100% receptive. A high-risk group was defined as >5 partners, <100% use of condom and ≥50% receptive intercourse. Univariate logistic regressions were applied to assess the association between sexual behaviours and the risk of each STI. Results: Out of 1051 MSM with at least one STI diagnosis, 580 (55%) answered the survey. The risk of chlamydia was lower among individuals with ≤5 partners (≤5 partners vs >5 partners: OR=0.43, 95% CI 0.28 to 0.66, p=0.001) and among those using condoms more frequently (≤50% use of condom vs >50% use of condom: OR=1.55, 95% CI 1.06 to 2.27, p=0.025; 100% vs <100%: OR=0.35, 95% CI 0.20 to 0.59, p=0.001). Individuals using condoms more frequently also had lower risk of gonorrhoea (100% use of condom vs <100% use of condom: OR=0.37, 95% CI 0.17 to 0.79, p=0.011). The risks of chlamydia (OR=3.07, 95% CI 1.92 to 4.90, p<0.001) and gonorrhoea (OR=2.05, 95% CI 1.12 to 3.75, p=0.020) were higher among individuals belonging to the high-risk group. Conclusions: Chlamydia and gonorrhoea are more likely associated with high-risk sexual behaviours than syphilis and anal HPV among MSM living with HIV.